Evaluation of microphthalmia associated transcription factor (MITF) expression in peripheral blood of a population with malign melanoma and control population and cell lines (2009)
Background: The incidence of malign melanoma tumours has increased more rapidly than any other type of cancer; this has intensified the searching for tools that facilitate early detection of melanoma. Microphthalmia associated transcription factor (MITF) is currently known as being a master melanocyte regulator. The article analyses MITF gene expression in peripheral blood of individuals suffering from melanoma, compared to people without any type of cancer and some cell lines. Materials and methods: Thirty one samples of peripheral blood were used: 19 from patients having melanoma and 12 from healthy people. Then RNA was extracted from these samples. MITF and housekeeping genes (?2M and GAPDH) expression levels were then quantified by real-time PCR. Five cell lines were also used to determine the MITF expression. Results: MITF gene expression could be observed in all individuals, though no statistical significant differences were found among expression levels in the groups studied (p=0.09). Even so, MITF expression in the group of patients suffering from melanoma was much more variable than that observed in the group of cancer-free people. Expression was detected in the cell line AGS (gastric adenocarcinoma), not yet described. Conclusions: MITF gene expression levels were detected in the peripheral blood from both people suffering from melanoma and people without any type of cancer. However, variability in the number of molecules in MITF gene expression was observed in people with melanoma, this suggests the presence of tumour cells in circulation. © 2009 Universidad del Valle, Facultad de Salud.